Penerapan Asuransi Dan Akad Murabahah Pada Pembiayaan KPR Di BTN Syariah KC Bandung - Juniarti, Ira; Sumiati, Dede; Rosinawati, Dian (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2023)
Mortgage financing to provide livable and comfortable housing by simply providing a down payment, and the rest is paid in installments every month. Mortgage financing also includes insurance coverage to anticipate if a customer dies and a way for the bank to minimize losses and risks. Qualitative research was conducted to find out the Application of Insurance and Murabahah Contracts in KPR Financing at BTN Syariah KC Bandung which was carried out by studying literature related to Islamic Banking, interviews, and financing procedures. The results of this study are that the application of a murabahah contract at BTN Syariah KC Bandung is used to provide mortgage financing in accordance with the results of the analysis carried out by the bank on prospective customers. First, the bank will inform the assessment of the location and house that the customer wants to own, fit to live in, and is considered comfortable to live in. Second, the customer prepares the required documents for submitting mortgage financing at the BTN Syariah bank. Third, the BTN Syariah bank will consider and assess the completeness of the prospective customer's files, as well as carry out a 5C analysis of the prospective Bank BTN Syariah KPR customers. Fourth, if the results of the analysis are feasible to finance, then proceed to the KPR financing disbursement stage. Fifth, installment payments are made every month according to the agreed period. Furthermore, the application of insurance to KPR financing at BTN Syariah KC Bandung in the form of a customer before signing in front of a notary, the bank asks the customer to prepare a down payment of 10–20% of the property price, booking fee fee, 1% provision fee of the total ceiling, fees credit agreement notary, APHT guarantee costs around 0.25% of 125% credit value, deed of sale and transfer of title, costs of acquisition of building land rights (BPHTB), fire insurance costs, and credit life insurance costs.